2009
DOI: 10.1063/1.3148075
|View full text |Cite
|
Sign up to set email alerts
|

Extended Lagrangian Born–Oppenheimer molecular dynamics with dissipation

Abstract: Stability and dissipation in the propagation of the electronic degrees of freedom in time-reversible extended Lagrangian Born-Oppenheimer molecular dynamics [Niklasson , Phys. Rev. Lett. 97, 123001 (2006); Phys. Rev. Lett. 100, 123004 (2008)] are analyzed. Because of the time-reversible propagation the dynamics of the extended electronic degrees of freedom is lossless with no dissipation of numerical errors. For long simulation times under ``noisy'' conditions, numerical errors may therefore accumulate to lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
244
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(248 citation statements)
references
References 77 publications
4
244
0
Order By: Relevance
“…In practice, for the numerical propagation of the matrix X, we use an equation of motion with a dissipative term to maintain the numerical stability of the matrix X. 34) In our previous study, we clarified the effects of control parameters used in the DMM method in the FPMD simulations. We found that, even when the total energy is not fully converged, MD trajectories are almost the same as those in more accurate MD simulations.…”
Section: Which Shows That X(t) Is Time-reversible and Evolves In A Hamentioning
confidence: 99%
“…In practice, for the numerical propagation of the matrix X, we use an equation of motion with a dissipative term to maintain the numerical stability of the matrix X. 34) In our previous study, we clarified the effects of control parameters used in the DMM method in the FPMD simulations. We found that, even when the total energy is not fully converged, MD trajectories are almost the same as those in more accurate MD simulations.…”
Section: Which Shows That X(t) Is Time-reversible and Evolves In A Hamentioning
confidence: 99%
“…This algorithm may also be used in conjunction with other methods to accelerate the simulations even further, such as the Langevin dynamics [5][6][7][8] , linear scaling method [24][25][26] and mass scaling method 27 . …”
Section: Discussionmentioning
confidence: 99%
“…14,15,60,64 In this paper, first principles free energy molecular dynamics schemes were developed based on extended Lagrangian Born-Oppenheimer molecular dynamics. 3,4,10,34 The formulation was given both for density matrix and plane wave representations. The density matrix formulation has numerically convenient expressions for the electronic forces as well as a recursive Fermi operator expansion that are well suited for reduced complexity calculations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This term corresponds to a weak coupling to an external system that removes numerical error fluctuations, but without any significant modification of the microcanonical trajectories and the free energy. 34 A few optimized examples of the dimensionless parameter, δt 2 ω 2 , the c k coefficients and α are given in Table I (see Ref. 34 for details). The integration coefficients in Table I are optimized under the condition of stability under incomplete, approximate SCF convergence.…”
Section: A Density Matrix Integrationmentioning
confidence: 99%
See 1 more Smart Citation